Import Trade of Mineral Resources Industry on Green Total Factor Productivity the Influence of the Study - Liu, Ningning (International Journal of Electric Power and Energy Studies, 2025)
To promote the green transformation and upgrading of the mineral resources industry under the background of "double-carbon", we should pay attention to the green total factor productivity (GTFP) to measure the industrial production efficiency and environmental impact. With the acceleration of globalization, import has become an effective way to improve the green total factor productivity (GTFP) of the mineral resources industry. This paper aims to explore the influence of import trade in mineral resources industry on green total factor productivity (GTFP), and analyze the mechanism of scale, structure and efficiency of import trade on GTFP by constructing econometric model. It is found that the moderate import trade of mineral resources can promote the technological progress and the introduction of management experience, so as to improve the GTFP of the mineral resources industry. However, excessive reliance on imports may lead to decreased domestic industrial competitiveness and have a negative impact on GTFP. Therefore, this paper proposes a series of policy suggestions, aiming to balance the relationship between the mineral resources import trade and the sustainable development of domestic industry.